Raman Spectroscopy Based Approach For The Discrimination And Characterization Of Streptococcus Thermophilus - Stela, P.; Marta, N.; Luiz, Z. (My University, 2020)
Streptococcus thermophilus is a thermophilic lactic acid bacterium used mainly for the preparation of dairy products, such as yogurt, other fermented milk, and cheeses. One of the main roles of S. thermophilus in milk fermentations is to provide rapid acidification. © 2020, Interamerican Society for Electron Microscopy (CIASEM). All rights reserved.
Keywords: Food-Grade Recombinant; Streptococcus Thermophilus; Urease Genes